Weaving the networks of history. Carlos Forcadell in Contemporary History - Frías Corredor, Carmen; Rújula López, Pedro; Sabio Alcutén, Alberto (Huarte de San Juan. Geografía e Historia, 2016)
This special issue is published to mark the recent retirement of Carlos Forcadell Álvarez, former Professor of Contemporary History at the University of Zaragoza and newly entitled Professor Emeritus. This article brings the opportunity to outline his professional career as a historian. This work focuses on three of his most prominent facets. The first one highlights his development as Professor and Research Director. The second one underlines his work on diverse fields such as social history, history of Aragon, economic history or historiography history. And the third one stresses on his managing capability, his ability to form research teams and develop projects. Ultimately, an attempt which’s aim is to establish the main professional activity of a key historian for the development of the contemporary heritage in Spain nowadays.